Fabrication of Cargocycle: The Ultimate Bicycle Redesign for Extra Luggage - Basra Bariya; Tushar S.Wankhede; Suraj R.Yadav; Shubham P.Burkunde; Taffazzul Ahmad (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The redesign of traditional bicycles for enhanced cargo-carrying capacity addresses the growing need for sustainable, efficient, and practical transportation solutions. Cargo Cycle ensures a smooth and stable riding experience. Whether for urban commuters, or delivery professionals, this innovative bike offers a reliable and efficient way to transport extra luggage, Cargo Cycle not only enhances transportation efficiency but also supports a cleaner, greener future for urban and rural mobility. This research paper explores the design considerations required to integrate cargo space into the traditional bicycle without compromising the bike’s performance, stability, and overall functionality. By focusing on the re-editing or redesigning of the older bicycle frame, this paper aims to provide innovative solutions for adding cargo capacity that improves the bike’s load-bearing ability, maneuverability, and rider comfort.